2016
DOI: 10.1002/app.43598
|View full text |Cite
|
Sign up to set email alerts
|

Influence of modification process parameters on the properties of crumb rubber/EVA modified asphalt

Abstract: Crumb rubber (CR) and ethylene vinyl acetate copolymer (EVA) were adopted as asphalt modifiers. Routine tests, softening point, penetration, and ductility were used to evaluate the basic properties of crumb rubber and ethylene vinyl acetate copolymers (CR/EVA) modified asphalt. The segregation experiment measured the storage stability. Modern test methods such as fluorescence microscopic photography technology was used to study stability of polymer modified asphalt. Infrared spectrum experiment was used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
(19 reference statements)
1
16
0
5
Order By: Relevance
“…Fang et al by investigating the effect of crumb rubber/ethylene vinyl acetate copolymer on asphalt mixture properties indicated that the softening point difference was almost less than 2.5 degrees. Moreover, the compatibility of modifiers and asphalt improved to a certain extent, and the degree of segregation became small and the storage became steady [52], which is in accordance with the results of this research. However, some studies have not conducted this test, and in order to decrease segregation, Table 9: e properties of cellulose fibers used.…”
Section: Segregation Test Resultssupporting
confidence: 91%
“…Fang et al by investigating the effect of crumb rubber/ethylene vinyl acetate copolymer on asphalt mixture properties indicated that the softening point difference was almost less than 2.5 degrees. Moreover, the compatibility of modifiers and asphalt improved to a certain extent, and the degree of segregation became small and the storage became steady [52], which is in accordance with the results of this research. However, some studies have not conducted this test, and in order to decrease segregation, Table 9: e properties of cellulose fibers used.…”
Section: Segregation Test Resultssupporting
confidence: 91%
“…As represented in Table that after the segregation test, the difference in softening point of each group of modified asphalt considerably changed. The difference in softening point of GNPs modified asphalt was 3.5 °C suggesting prone nature of GNPs and in turn the resulting modified asphalt to segregated agglomeration . On the contrary, the difference in softening point of C 4 H 9 ‐GO‐modified asphalt (0.3 °C) was lower than that of SBS‐modified version indicating higher resistance to segregation of the former than the latter.…”
Section: Resultsmentioning
confidence: 92%
“…Each TPV sample obtained from a previous section was cut into small pieces (≤2 mm) and gradually mixed with asphalt at 5 wt% using a high-speed shear mixer (L5M model, Silverson, Massachusetts, USA) at 150 °C with a rotor speed of 6000 rpm for 2 h and 3000 rpm for 2 h in order to remove air bubbles from asphalt. The protocol was adapted from Fang et al [ 35 ]. The suitable condition to mix EVA and crumb rubber (CR) with asphalt were a mixing temperature of 140 °C, mixing time of 1.5 h, and rotor speed of 3750 rpm.…”
Section: Methodsmentioning
confidence: 99%